0276 Association of Actigraphic Sleep Parameters with Fatigability in Older Adults. (27th April 2018) - Alfini, A J; Schrack, J A; Urbanek, J K; Simonsick, E M; Zipunnikov, V; Spira, A P
Abstract: Introduction: Sleep disturbances increase with age and are linked to morbidity and functional decline. Similarly, fatigue is common among older adults and is associated with poor health outcomes. Although insufficient sleep may exacerbate fatigue, most studies have relied on subjective sleep and fatigue measures, or have used clinical samples. We investigated the association of actigraphic sleep parameters with measures of fatigability—fatigue in response to a standardized task—in a community-based sample of older adults. Methods: Participants were 243 community-dwelling older adults from the Baltimore Longitudinal Study of Aging aged 72 ± 12 years (44% women) who completed 6.8 ± 3.4 days of wrist actigraphy and two fatigability assessments: the Pittsburgh Fatigability Scale (PFS) and a subjective rating of perceived exertion (Borg RPE; 6–20) after a 5-min, 1.5 mph treadmill walk. Our primary predictors were total sleep time (TST), sleep efficiency (SE), sleep onset latency (SOL), and average wake-bout-length during sleep (WBL). Results: In models adjusted for age, sex, and BMI, each five-percent increase in SE was associated with a 0.21-unit decrease in RPE (ß = -0.21, p = 0.039), each five-minute increase in SOL was associated with a 0.18-unit increase in RPE (ß = 0.18, p = 0.016), and each one-minute increase in WBL was linked to a 1.29-point increase on the PFS (ß = 1.29, p = 0.034). Aside from WBL, these associations remained after adjusting for number of comorbidities (SE ß = -0.22, p = 0.036; SOL ß = 0.18, p = 0.014). There was no association between TST and either fatigability measure. Conclusion: Among older adults, actigraphic indices of longer SOL, lower SE, and longer WBL are associated with greater fatigability in response to a standardized task. Prospective studies are needed to evaluate the direction of these associations and guide the development of interventions to improve sleep and curb fatigue in older adults. Support (If Any): Supported by National Institute on Aging (NIA) grants T32-AG027668, R01AG050507, RF1AG050745, R01AG049872, U01AG052445, R21AG053198, P30AG021334, U01AG057545, the NIA Intramural Research Program and HHSN-260-2004-00012C.